Environmental impacts of the water footprint and waste generation from inputs used in the meals of workers in a Brazilian public hospital (Research, Society and Development, 2021)
This study aimed to assess the environmental impacts of waste generation and the WF of raw materials used to provide meals to workers in a public hospital in southern Brazil over the course of the four seasons. This is a descriptive case study with a quantitative approach. The food raw materials that composed meals during 2019 were grouped by type of input. The items included from each food group were those which represented at least 85% (Multiple Criteria ABC Analysis) of the total amount used in kilograms within the respective group, in each month. The generation of residues from fruits, vegetables, and meat was estimated, as well as the WF of the items. For the statistical analysis, the Kruskal-Wallis test was used with a significance of 5%. Out of the 96 food inputs used, 49 items represented 86% of the total in kg, being the ones from which the environmental impacts were calculated. During the year, 435,411 meals were served. As for the number of diners, the highest frequency was observed in the winter and lowest in the summer. The annual waste percentage of the fruits acquired was 33.8%, being higher in the summer than in other seasons. Animal products were responsible for 64.2% of the WF, being higher in the winter. Assessing user frequencies, climatic conditions, and raw-material selection are important measures for the appropriate management of foodservices, as well as for assessing their environmental impacts.